SOCIAL, MORAL PSYCHOLOGICAL PROBLEMS IN THE WORKS OF CHARLES PERSY SNOW - Kozakova Oydin (Лучшие интеллектуальные исследования, 2023)
Abstract: This article talks about the depiction of social and psychological problems in the work of Charles Percy Snow and how the writer managed to convey these problems and the solutions to such problems to the reader.